﻿Visões de um quadro complexo: a violência policial no espelho das representações sociais - Mendes, Marcos Baptista (2007)
﻿In the last three decades, the Brazilian social dynamics evidenced increasing requirements in the public security, in the search not only for efficient and efficient police institutions, however that they added in its daily one, positions more adjusted to the Democratic State of Right and a bigger respect to the human rights and the citizenship. In this direction, the practical one of the police violence has been hardly debated in the media and the academics institutions, in the search for elements that clarify its roots and elements of intervention that allow to its control and reduction. The research considers, from the study of the social representations constructed by the soldiers of the Military Policy of the Rio Grande do Norte, having as objects the police violence, searching to evidence the central elements of these representations and its practical reproduction in the daily one, while a products of habitus effective in the institution